Nothing about me without me: a scoping review of how illness experiences inform simulated participants' encounters in health profession education. (17th June 2021) - Ní Chianáin, Linda; Fallis, Richard; Johnston, Jenny; McNaughton, Nancy; Gormley, Gerard
Abstract : Background: Person-centred simulation in health professions education requires involvement of the person with illness experience. Objective: To investigated how real illness experiences inform simulated participants' (SP) portrayals in simulation education using a scoping review to map literature. Study selection: Arksey and O'Malley's framework was used to search, select, chart and analyse data with the assistance of personal and public involvement. MEDLINE, Embase, CINAHL, Scopus and Web of Science databases were searched. A final consultation exercise was conducted using results. Findings: 37 articles were within scope. Reporting and training of SPs are inconsistent. SPs were actors, volunteers or the person with the illness experience. Real illness experience was commonly drawn on in communication interactions. People with illness experience could be directly involved in various ways, such as through conversation with an SP, or indirectly, such as a recording of heart sounds. The impact on the learner was rarely considered. Conclusion: Authentic illness experiences help create meaningful person-centred simulation education. Patients and SPs may both require support when sharing or portraying illness experience. Patients' voices profoundly enrich the educational contributions made by SPs.